ANALISIS MAKNA SIMBOLIK KOMUNIKASI NONVERBAL OLEH GURU KELAS VII-I DI SMP NEGERI 1 SUNGAI RAYA - Mayasari, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis thesis is titled, Analysis Simbolic Meaning Nonverbal Communication by Teacher Class VII-I in SMP Negeri 1 Sungai Raya. A common problem in study is, how the simbolic meaning touch by the teacher and learning process in SMP Negeri 1 Sungai Raya?. General purpose in research is analyzing the symbolic meaning touch by the teacher and learning process in SMP Negeri 1 Sungai Raya. The approach used in this research is qualitative approach with descriptive method. Data collection techniques used observation techniques, interview guides, and documentation. Who became informants in this study were IPS teacher and student of class VII-I in SMP Negeri 1 Sungai Raya.The results of this study show that, in Â process of teaching and learning in class VII-I teacher use nonverbal communication to support verbal communication. The nonverbal communication used is touch symbol. In using touch symbols, the teacher uses three meanings of touch symbols ie touch shake hands, touches open or embrace, and touch reach. Touch shake hands meaningful friendship. Touch open or embrace meaningful reinforcement. Touch embrace meaningful affection. So symbolic meaning touch is expression body gestures in giving frienship, reinforcement, affection, openness and rebuke are not directly expressed directly by informant.Â Keywords: Simbolic meaning nonverbal communication, touch by the teacher.Â